Novel plant–frugivore network on Mauritius is unlikely to compensate for the extinction of seed dispersers - Heinen, Julia H.; Florens, F. B. Vincent; Baider, Cláudia; Hume, Julian P.; Kissling, W. Daniel; Whittaker, Robert J.; Rahbek, Carsten; Borregaard, Michael K. (Nature communications, 2023)
Insular communities are particularly vulnerable to anthropogenic extinctions and introductions. Changes in composition of island frugivore communities may affect seed dispersal within the native plant community, risking ecological shifts and ultimately co-extinction cascades. Introduced species could potentially mitigate these risks by replacing ecological functions of extinct species, but conclusive evidence is lacking. Here, we investigate changes in plant–frugivore interactions involving frugivorous birds, mammals and reptiles in Mauritius, an oceanic island with an exceptionally well-specified frugivore community and well-described species introduction history. We demonstrate substantial losses of binary interaction partnerships (at the species level) resulting from native species extinctions, but also gains of equal numbers of novel interactions with introduced species, potentially supporting the idea that non-native species might compensate for lost seed dispersal. However, closer investigation of animal seed handling behaviour reveals that most interactions with seed dispersers are replaced by ecologically different interactions with seed predators. Therefore, restoration of seed dispersal functionality in this novel plant–frugivore community is unlikely. Many plant species depend on frugivores for seed dispersal. Here, the authors investigate plant-frugivore networks in Mauritius, finding that the new interactions gained from the arrival of non-native seed predators are unlikely to compensate for the extinction of seed dispersers.